1990
DOI: 10.1177/105960119001500405
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Initial Interaction in Leader-Member Exchange

Abstract: The present research employed a correlational-design laboratory study to examine the initialinteraction component of a developmental model of Graen's leader-member exchange theory of leadership proposed by Dienesch and Liden (1986). The influence of ability, liking, and the three upward-influence tactics of ingratiation, assertiveness, and rationality on the quality of leadermember exchange was examined both from the perspective of group leaders and members. The 188 subjects were assigned to groups of 4 (a lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 22 publications
6
109
1
Order By: Relevance
“…This includes work on dyadic role-making processes (Graen, Orris, & Johnson, 1973;Haga, 1976;Graen, Novak, & Sommerkamp, 1982;Seers & Graen, 1984;Snyder & Bruning, 1985;Zalesny & Graen, 1987;Graen & Scandura, 1987;Graen, 1989;McClane, 1991b), investigations of communication frequency (Schiemann & Graen, 1984;Baker & Ganster, 1985;Borchgrevink & Donohue, 1991), investigations of interactive communication patterns relative to LMX (Fairhurst & Chandler, 1989;Fairhurst, 1993), and leader-member value agreement (Graen & Schiemann, 1978;Kozlowski & Doherty, 1989;Ashkanasy & O'Connor, 1994). In addition, this category includes research on antecedents to and/or determinants of LMX Larwood & Blackmore, 1978;Kim & Organ, 1982;Duchon, Green, & Taber, 1986;Steiner, 1988;Heneman, Greenberger, & Anonyuo, 1989;Liden, Wayne, & Stilwell, 1993;Vasudevan, 1993), upward maintenance tactics and interaction patterns used by followers in high LMX relationships (Waldron, 1991), subordinate loyalty (Scandura & Graen, 1984), decision influence , influence tactics (Wayne & Ferris, 1990;Dockery & Steiner, 1990;Deluga & Perry, 1991), and member affect about the relationship (Liden, 1985;McClane, 1991a;Day & Crain, 1992). Moreover, studies investigating characteristics of followers in high LMX relationships identified them as high growth-need strength …”
Section: Stage 2: Focus On the Relationship And Its Outcomesmentioning
confidence: 99%
“…This includes work on dyadic role-making processes (Graen, Orris, & Johnson, 1973;Haga, 1976;Graen, Novak, & Sommerkamp, 1982;Seers & Graen, 1984;Snyder & Bruning, 1985;Zalesny & Graen, 1987;Graen & Scandura, 1987;Graen, 1989;McClane, 1991b), investigations of communication frequency (Schiemann & Graen, 1984;Baker & Ganster, 1985;Borchgrevink & Donohue, 1991), investigations of interactive communication patterns relative to LMX (Fairhurst & Chandler, 1989;Fairhurst, 1993), and leader-member value agreement (Graen & Schiemann, 1978;Kozlowski & Doherty, 1989;Ashkanasy & O'Connor, 1994). In addition, this category includes research on antecedents to and/or determinants of LMX Larwood & Blackmore, 1978;Kim & Organ, 1982;Duchon, Green, & Taber, 1986;Steiner, 1988;Heneman, Greenberger, & Anonyuo, 1989;Liden, Wayne, & Stilwell, 1993;Vasudevan, 1993), upward maintenance tactics and interaction patterns used by followers in high LMX relationships (Waldron, 1991), subordinate loyalty (Scandura & Graen, 1984), decision influence , influence tactics (Wayne & Ferris, 1990;Dockery & Steiner, 1990;Deluga & Perry, 1991), and member affect about the relationship (Liden, 1985;McClane, 1991a;Day & Crain, 1992). Moreover, studies investigating characteristics of followers in high LMX relationships identified them as high growth-need strength …”
Section: Stage 2: Focus On the Relationship And Its Outcomesmentioning
confidence: 99%
“…The relationship is initiated when the boss likes the worker and views him or her as capable and motivated (Dockery & Steiner, 1990). The social exchange within the in-group dyad enables the worker to assume more responsibility and to receive in return recognition and support from the leader.…”
Section: Management As a Social Interactionmentioning
confidence: 99%
“…see Dockery & Steiner, 1990;Vecchio & Sussman, 1991). This shift occurred as researchers realized that influence tactics not only affect subordinate's perceptions and resulting organizational outcomes, but also shape supervisors' perceptions and subsequent decisions.…”
Section: Articlementioning
confidence: 99%